Pengaruh suhu proses dan lama pengendapan terhadap kualitas biodiesel dari minyak jelantah (The influence of process temperature and deposition time on biodiesel quality of cooking oil) - Silvira Wahyuni; - Ramli; - Mahrizal (Department of Physics – Universitas Negeri Padang UNP, 2015)
Biodiesel is a type of fuel alternative diesel derived from biological materials that are processed vegetable oil transesterification using methanol and catalyst NaOH. One of the vegetable oil is used cooking oil. Used cooking oil is one of the raw materials that have a high chance for the manufacture of biodiesel because it still contains triglycerides in addition to free fatty acids. Biodiesel is made by giving some physical treatment, such as temperature and duration of settling time. To investigate the influence of temperature processes and duration settling time conducted this research with a variety of 40°C, 50°C, 60°C, 70°C, and 80°C and duration settling time , for 48 hours, 96 hours, 144 hours, 192 hours and 240 hours as independent variables, Controlled variable is the time stirring for 5 minutes, stirring speed of 1050 rpm, the catalyst base (NaOH), a methoxide liquid is 20%. Dependent Variable is biodiesel quality which covers viscosity, density, yield, and Flash Point. It was found if the temperature is greater, the viscosity and density decreases. While the highest yield is 76% produced by variations in temperature of 50°C, the average Flash point >110°C, the results of biodiesel according to the SNI Standards. For a settling time variety is not a significant influence in the making of biodiesel with the average for all variations in viscosity between 5.7-5.8 CSt, density of about 861 kg/m3, flash point >110°C and average yield is 75.8%